Practices of detecting and removing nuisance alarms for alarm overloading in thermal power plants. (October 2017) - Wang, Jiandong; Yang, Zijiang; Chen, Kuang; Zhou, Donghua
Abstract: Alarm overloading refers to the most noticeable phenomenon in existing alarm systems: there are far too many alarms to be promptly handled by industrial plant operators. A large number of occurred alarms are nuisance alarms that are not associated with any actual abnormalities and are extremely detrimental to important roles of industrial alarm systems. This paper presents long-term industrial applications of three techniques on detecting and removing nuisance alarms to a thermal power generation unit. By deploying these techniques, the severity of alarm overloading phenomenon has been significantly alleviated. The average number of alarm occurrences per day has been reduced from 18, 280 to 359 in the year of 2015, so that about 98% alarm occurrences have been removed without affecting true alarms. Highlights: Three techniques on detecting and removing nuisance alarms are reviewed or revised. Long-term applications of the techniques to a power generation unit are presented. 98% alarm occurrences have been removed without affecting true alarms. The severity of alarm overloading phenomenon has been greatly alleviated.